Research Progress on Regulation of Tumor-Associated Macrophages Polarization by Intratumoral Microorganisms in Pancreatic Cancer - Yan, Yaxian; Wang, Wei (Zhongliu fangzhi yanjiu, 2025)
Recent studies have revealed the presence of specific microorganisms in pancreatic cancer. Accumulating evidence suggests a correlation between changes in the microbiome and tumor immune function in pancreatic cancer. Various stimuli within the tumor microenvironment (TME) prompt the polarization of tumor-associated macrophages (TAMs) toward the immune-activating M1 phenotype or immunosuppressive M2 phenotype. Microorganisms in the TME can facilitate or inhibit tumor growth, metastasis, drug resistance, and other processes by influencing the phenotypes and functions of macrophages. This article reviews the mechanisms by which anaerobic bacteria regulate TAM polarization in the TME of pancreatic cancer. Additionally, it discusses the effects of bacterial components and metabolites on TAM polarization, aiming to provide new targets for the diagnosis and treatment of pancreatic cancer from a microbial perspective.